The Determinant Factors of Operational Performance in Indonesian Banking Companies - Sherlita, Erly (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the determinant factors of operational performance in the Indonesian banking companies. The factors tested include public funds, growth of earning assets, credit risks, liquidity risks, and capital adequacy on operational performance. The data use a new unbalanced data panel from 203 financial reports of 44 banking companies that are listed on the Indonesia Stock Exchange for the period 2013-2017.The results showed that public funds and the growth of earning assets have a significant negative effect on operational performance. Meanwhile, credit risk as measured by a non-performing loan has a significant positive effect on operational performance. However, this study found liquidity risk and leverage risk have no effect on operational performance.